2018
DOI: 10.1016/j.envpol.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment for fine particulate matter in a Chinese city using an improved gas-constrained method and comparison with multiple receptor models

Abstract: PM is one of the most studied atmospheric pollutants due to its adverse impacts on human health and welfare and the environment. An improved model (the chemical mass balance gas constraint-Iteration: CMBGC-Iteration) is proposed and applied to identify source categories and estimate source contributions of PM The CMBGC-Iteration model uses the ratio of gases to PM as constraints and considers the uncertainties of source profiles and receptor datasets, which is crucial information for source apportionment. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Shi et al [ 70 ] employed a chemical mass balance gas constraint-Iteration (CMBGC-Iteration) method for source appointment analysis in Tianjin. The outcomes from this method were compared with the ensemble-average outcomes of CMB, CMB-Iteration, CMB-GC, PMF, WALSPMF (Weighted Alternating Least Squares Positive Matrix Factorization), and NCAPCA (Non-negative Constrained Absolutely Principle Analysis), and it was found that they were comparable.…”
Section: Sources Of Pm 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al [ 70 ] employed a chemical mass balance gas constraint-Iteration (CMBGC-Iteration) method for source appointment analysis in Tianjin. The outcomes from this method were compared with the ensemble-average outcomes of CMB, CMB-Iteration, CMB-GC, PMF, WALSPMF (Weighted Alternating Least Squares Positive Matrix Factorization), and NCAPCA (Non-negative Constrained Absolutely Principle Analysis), and it was found that they were comparable.…”
Section: Sources Of Pm 25mentioning
confidence: 99%
“…The outdoor sources come from heating fuel, industry, traffic, etc. [ 34 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], due to the rapid industrialization, high energy consumption and large proportion of coal (60–70%) in the structure of energy sources in China. It has been acknowledged that there is close correlation between indoor and outdoor PM 2.5 concentration levels, and outdoor PM 2.5 is the main source of indoor PM 2.5 pollution [ 75 , 76 , 77 ].…”
Section: Sources Of Pm 25mentioning
confidence: 99%
“…chemical mass balance (CMB) and positive matrix factorization (PMF)) (Watson et al, 1990;Paatero, 1997;Paatero and Tapper, 1994), SOA-tracer method (Kleindienst et al, 2007) and radiocarbon ( 14 C) measurements (Szidat et al, 2009;GelencsĂ©r et al, 2007). These methodologies have been successfully applied worldwide and, in general, good agreements have been reported when compared by twos directly (Song et al, 2006;Kim et al, 2004;Kleindienst et al, 2010;Pachon et al, 2010;Heo et al, 2013;Al-Naiema et al, 2018;Srivastava et al, 2018b;Bove et al, 2018;Bae et al, 2019;Antony Chen and Cao, 2018;Hettiyadura et al, 2018;Jiang et al, 2018;Keerthi et al, 2018;Matawle et al, 2018;Shi et al, 2018;Shirmohammadi et al, 2016;Lanzafame et al, 2020). However, large discrepancies have been also observed when apportioning the SOA fraction, depending on the methods compared, the period of the year considered or atmospheric conditions observed (Srivastava et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial factors, biomass burning, and other sources individually contributed 13%, 4%, and 15%. After 2013, the percentage of dust dropped to 16%, while the contribution of coal burning, traffic, and secondary source separately risen to 19%, 15%, and 24% [61,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88], and they were the top four sources as before. This shows that the treatment project of sandstorm sources of Beijing and Tianjin has achieved preliminary success in recent years.…”
Section: Major Source Of Haze Pm In Different Regionsmentioning
confidence: 94%